NCMP-02. RENAL CELL CARCINOMA WITH METASTASIS TO THE CHOROID PLEXUS. (14th November 2022) - Kim, Emily; Nadeem, Danial; Nguyen, James; Ammar, Hussam
Abstract: BACKGROUND: Intraventricular brain tumors make up only 0.9–4.5% of all cases of metastatic brain cancer. 1 Involvement of the choroid plexus (CP) is even rarer with only a handful of documented cases. 2, 3 Here we describe a case of bilateral multifocal metastasis to the choroid plexus appearing 10 years after nephrectomy in a male with stage IV renal cell carcinoma (RCC). CASE PRESENTATION: Our patient is a 74-year-old male with stage IV RCC diagnosed in 2006 and treated with radical nephrectomy and immunotherapy in 2011. In 2020, he presented to the emergency department with altered mental status. Brain magnetic resonance imaging (MRI) revealed an enhancing hemorrhagic lesion in the trigone of the right lateral ventricle (LV) and nodular thickening in the center of the right LV and trigone of the left LV, suggestive of metastatic disease. In 2021, the patient developed refractory seizures, and serial MRIs showed disease progression. He underwent several craniotomies with pathology confirming metastatic clear cell carcinoma, consistent with a renal primary. In 2022, the patient again presented with altered mental status. MRI revealed new avidly enhancing subcentimeter solid nodules in the CP of both LVs consistent with metastatic disease. Per the wishes of the family, palliative measures were pursued, and the patient was discharged home. CONCLUSION: RCC can reappear several years after nephrectomy. 4 Metastatic RCC appears to have a unique propensity to spread to the ventricular system and the CP, which indicates late progression of disease. 1, 5, 6 While surgery may be viable if tumor burden is low, therapeutic options are limited in the advanced disease stages, as in our patient. Palliative care should be offered early to maximize remaining quality of life.